Digital Transformation in the Tariff Monitoring and Evaluation Division BP Batam (Transformasi Digital di Divisi Pemantauan dan Evaluasi Tarif BP Batam) - Amanda, Nasyah; Zai, Immanuel (Indonesia Berdaya, 2025)
This program aims to shift the use of paper media in the tariff fairness evaluation activities of the Tariff Monitoring and Evaluation Division at BP Batam to digital media. Information is gathered through employee interviews and surveys. By transitioning to digital media, increased efficiency and reduced operational costs are expected, as well as a positive environmental impact through reduced paper usage.Abstrak: Program ini bertujuan untuk mengalihkan penggunaan media kertas dalam kegiatan evaluasi kewajaran tarif di Divisi Monitoring dan Evaluasi Tarif BP Batam ke media digital. Informasi dikumpulkan melalui wawancara dan survei karyawan. Dengan beralih ke media digital, diharapkan terjadi peningkatan efisiensi dan pengurangan biaya operasional, serta dampak positif terhadap lingkungan melalui pengurangan penggunaan kertas.